Systematic Journal Review: Literasi Kritis sebagai Strategi Menghadapi Brain Rot pada Anak Remaja Awal - Switia Dewi Quraisyin; Eva Leiliyanti; Siti Gomo Attas (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
The rapid development of digital technology and the high intensity of social media consumption among early adolescents have contributed to the emergence of brain rot, which negatively affects cognitive functioning. This condition highlights the urgency of examining critical literacy as an educational strategy to strengthen adolescents’ cognitive resilience. This study aims to systematically analyze the role of critical literacy in addressing brain rot among early adolescents based on recent scientific evidence. This study employed a systematic journal review design guided by the PRISMA framework. Relevant articles were retrieved from multiple international and national databases using strict inclusion criteria. A total of ten primary studies were analyzed through thematic synthesis. The findings indicate that excessive digital media consumption is associated with decreased attention, memory impairment, and shallow cognitive engagement among early adolescents. Critical literacy was found to enhance reflective and evaluative thinking as well as awareness of algorithmic manipulation in digital media. Moreover, the integration of critical literacy supports improved self-regulation and cognitive resilience. In conclusion, critical literacy represents an effective preventive and corrective strategy in addressing brain rot among early adolescents.